Virtual elements for Maxwell's equations. (15th June 2022) - Beirão da Veiga, L.; Dassi, F.; Manzini, G.; Mascotto, L.
Abstract: We present a low order virtual element discretization for time dependent Maxwell's equations, which allow for the use of general polyhedral meshes. Both the semi- and fully-discrete schemes are considered. We derive optimal a priori estimates and validate them on a set of numerical experiments. As pivot results, we discuss some novel inequalities associated with de Rahm sequences of nodal, edge, and face virtual element spaces.